Preparation and characterization of mesostructured functional materials with different morphologies - Aiello, Daniela; Aiello, Rosario; Testa, Flaviano; Molinari, Raffaele (My University, 2008)
Mesoporous materials with their good surface and structural properties and versatility can be synthesized in different morphologies (thin films, fibers, membranes, etc.) and represent excellent host matrices, highly functional and with great potentials for advanced applications. In this research work, mesoporous powders and thin films have been successfully achieved and then functionalized with special guest molecules such as organic molecules, organometallic complexes, fluorescent dyes, all having specific and interesting properties. Mesoporous matrices have been prepared by sol-gel chemistry with different mesostructures and high order degree. Chemical modifications approaches (post-synthesis grafting and one-pot synthesis) applied to porous supports highly organized have allowed to product a new class of functional materials, particularly interesting for various applications (opto-electronic, photovoltaic materials, etc.). Surface and structural characterization techniques (FTIR, UV-Vis, fluorescence, ellipsometry spectroscopies, electron transmission microscopy, XRD diffraction and porosimetry analysis) have allowed to investigate the effects of the introduction of guest species inside mesoporous matrices and to identify noteworthy changes about organization and mesostructures. Results show that mesoporous materials, both as powders and thin films, do not suffer significant reductions of surface (surface area, pore volume and diameter) and structural properties (order degree, mesostructure organization, stability) after functionalization process, representing confined environment well adapted to various guest species, with the advantage to increase their activity and physic-chemical properties. In particular, guest species are well trapped into rigid porous matrices with an increase of their functional properties and inorganic network stability. All results have demonstrated that the high structural homogeneity, the control over surface and morphological properties and also the possibility to host different molecules permit to project and engineer high potential technological materials for applications in optic and electro-optic fields.
Course in Chemical and Materials Engineering, Ciclo XXI, a.a. 2007-2008
Keywords: Ingegneria Chimica; Materiali; Nanotecniologia; Film sottili; Ottica